PEMAHAMAN KONSEP DALAM PEMBELAJARAN MATEMATIKA - Budi Mulyono; Hapizah Hapizah (FKIP Universitas Muhammadiyah Prof. DR. HAMKA, 2018)
This article discusses about what conceptual understanding is in learning of mathematics and how conceptual understanding could be developed in a student’s thinking. As we know, generally, at least there are two types of learning that we have already experienced until right now, they are rote learning and meaningful learning, where each type has itself characteristic different from each other. The fundamental difference between the two types of learning is that rote learning emphasizes on memorizing structurally meanwhile meaningful learning focusing on understanding concepts learned. Therefore, teachers should carefully consider suitable strategies of teaching before deciding which types of learning could be developed in students’ thinking, and teachers need to pay attention to the effectiveness of teaching and learning in order to help students achieving a conceptual understanding.